2017
DOI: 10.1186/s13046-017-0507-3
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling plays a crucial role in cancer stem-like cells maintaining stemness and mediating chemotaxis in renal cell carcinoma

Abstract: BackgroundCancer stem cells (CSCs) are correlated with the initiation, chemoresistance and relapse of tumors. Notch pathway has been reported to function in CSCs maintenance, but whether it is involved in renal cell carcinoma (RCC) CSCs maintaining stemness remain unclear. This study aims to explore the effect of Notch pathway on stemness of CSCs in RCC and the underlying mechanisms.MethodsThe CD133+/CD24+ cells were isolated from RCC ACHN and Caki-1 cell line using Magnetic-activated cell sorting and identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 46 publications
(46 reference statements)
3
108
0
Order By: Relevance
“…We performed a series of in vitro and in vivo studies to obtain evidence that the decreased expression of miR-34a significantly contributes to lung and liver metastasis and chemoresistance through the inhibition of apoptosis and the JAG1/Notch1 axis in PC. Accumulating evidence shows that the induction of apoptosis and activation of Notch1 signaling pathways dramatically suppresses tumor growth, metastasis, and chemoresistance, including in PC [21,35,36]. Our data clearly showed that the overexpression of miR-34a significantly enhanced paclitaxel-induced apoptosis and Notch1 signaling pathway inhibition and dramatically inhibited PC metastasis in vivo, which indicates that the restoration of miR-34a may be a useful strategy for the treatment of metastasis and chemoresistance, in PC patients.…”
Section: Discussionsupporting
confidence: 49%
“…We performed a series of in vitro and in vivo studies to obtain evidence that the decreased expression of miR-34a significantly contributes to lung and liver metastasis and chemoresistance through the inhibition of apoptosis and the JAG1/Notch1 axis in PC. Accumulating evidence shows that the induction of apoptosis and activation of Notch1 signaling pathways dramatically suppresses tumor growth, metastasis, and chemoresistance, including in PC [21,35,36]. Our data clearly showed that the overexpression of miR-34a significantly enhanced paclitaxel-induced apoptosis and Notch1 signaling pathway inhibition and dramatically inhibited PC metastasis in vivo, which indicates that the restoration of miR-34a may be a useful strategy for the treatment of metastasis and chemoresistance, in PC patients.…”
Section: Discussionsupporting
confidence: 49%
“…Finally, it is well recognised that highly conserved developmental pathways such as Notch, Wnt, and Hedgehog are critical for the regulation of self-renewal in both embryonic and adult stem cells, and hence are likely to be implicated in the maintenance of cancer stem cells [43] ; Notch inhibition resulted in partial loss of its stemness features, i.e., self-renewal, chemoresistance, the invasive and migratory potential, and tumorigenesis in vivo [43] .…”
Section: Resultsmentioning
confidence: 99%
“…CD133 is considered to be the most common CSC marker, and has been used repeatedly for the successful isolation of osteosarcoma stem cells [19]. A growing number of studies have found that using immunomagnetic double positive screening could obtain CSCs with higher purity and stemness [20,21]. In this study, stem cell like cells were obtained from osteosarcoma cells by CD133+/CD44+ immunomagnetic beads double positive screening method and the isolated CD133+/CD44+ CSCs were identified by flow cytometry analysis.…”
Section: Egcg Inhibited Dox-induced Autophagy By Targeting Sox2ot V7mentioning
confidence: 98%